(untitled) (Research, Society and Development, 2024)
The general objective of this study is to analyze the role of the psychologist in the treatment of autistic children, based on the principles of Applied Behavior Analysis (ABA). Autism Spectrum Disorder (ASD) is a condition characterized by difficulties in communication, social interaction, and restricted and repetitive behaviors, requiring specific therapeutic approaches to develop the child’s skills. ABA is a scientific methodology widely recognized and used in the treatment of children with ASD, focusing on modifying behaviors and promoting functional learning. The psychologist, as a central professional in this process, plays a crucial role in the application of ABA, creating individualized interventions that aim to improve the social, communicative, and academic skills of patients. The literature review indicates that the role of the psychologist, in partnership with other professionals and the family, is fundamental for therapeutic success. Furthermore, the challenges and possibilities for improvement in professional practices and therapeutic approaches are discussed, highlighting the importance of continuous training for the professionals involved and the need for further research to broaden the understanding of the application of ABA in different contexts.